2005
DOI: 10.1007/s10495-005-6069-4
|View full text |Cite
|
Sign up to set email alerts
|

Antiapoptotic role of p38 mitogen activated protein kinase in Jurkat T cells and normal human T lymphocytes treated with 8-methoxypsoralen and ultraviolet-A radiation

Abstract: A combination of 8-methoxypsoralen and ultraviolet-A radiation (320-400 nm) (PUVA) is used for the treatment of T cell-mediated disorders, including chronic graft-versus-host disease, autoimmune disorders, and cutaneous T-cell lymphomas. The mechanisms of action of this therapy, referred to as extracorporeal phototherapy, have not been fully elucidated. PUVA is known to induce apoptosis in T lymphocytes collected by apheresis, however no information is available concerning the underlying signaling pathways whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…Although the activation of p38 MAPK signaling is classically related to stress responses and activation of cell death (51), there is increasing evidence that under certain circumstances p38 MAPK can enhance cell survival. Indeed, p38 MAPK activation has been demonstrated to enhance cell survival responses to DNA damage (52,53 (55). Although these investigations have provided important information regarding modulation of host immunity by Congo Basin MPXV, the integration of systems kinomics has provided pertinent functional information regarding the differential host response to Congo Basin MPXV and the less-virulent West African MPXV clade and identified potential host targets for therapeutic intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Although the activation of p38 MAPK signaling is classically related to stress responses and activation of cell death (51), there is increasing evidence that under certain circumstances p38 MAPK can enhance cell survival. Indeed, p38 MAPK activation has been demonstrated to enhance cell survival responses to DNA damage (52,53 (55). Although these investigations have provided important information regarding modulation of host immunity by Congo Basin MPXV, the integration of systems kinomics has provided pertinent functional information regarding the differential host response to Congo Basin MPXV and the less-virulent West African MPXV clade and identified potential host targets for therapeutic intervention.…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that down-regulation of FOXO1A results in the nuclear export of p27(Kip1) and that reactivation of FOXO1A also restores the growth-inhibitory effects of trastuzumab on SK-BR-3 cells. 34 Moreover, P38 MAPK has been shown to play an important role in cell growth regulation and to have antiapoptotic ability not only in T lymphocytes 35 and smooth muscle cells 36 but also in cancer cells. 37 Our results demonstrate that SWT reverses trastuzumabinduced cytotoxicity in SK-BR-3 and BT-474 cells, partly through activation of AKT signaling and suppression of p27(Kip1) function and partly through activation of the P38 MAPK pathway.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that the SAPK pathways can also induce apoptosis through the death-receptor pathway (280,282). Conversely, JNK or p38 MAPK activation has been reported to have an antiapoptotic effect in malignant B and T lymphocytes, respectively (41,191). The bifunctional role of the SAPK pathways in cell-fate decision may be dependent on different cell types and stimuli.…”
Section: Trachootham Et Al 1352 Fig 7 Redox Regulation Ofmentioning
confidence: 99%